Empowering leadership and frontline employees’ emotional labor: the mediation effects of job passion - Cheng, Pengfei; Zhou, Linfei; Liu, Tong; Ge, Na (Frontiers in Psychology, 2025)
InstructionIn order to deliver superior service experience to customers, frontline employees must regulate their emotional expressions during service encounters. This study examines how empowering leadership influences emotional labor (deep acting and surface acting) through the mediating role of job passion.MethodsUsing data of 1,040 frontline employees across three service industries, the proposed mediating model was tested.ResultsThe findings revealed that: empowering leadership predicted deep acting and reduced surface acting. Job passion mediated the relationship between empowering leadership and emotional labor. Specifically, empowering leadership influenced surface acting only through obsessive passion. Empowering leadership had a “double-edged” effect on deep acting, operating through both harmonious and obsessive passion simultaneously.DiscussionThis study highlights the mediating role of job passion in translating empowering leadership into emotional labor strategies. The findings help service organizations refine leadership strategies to enhance emotional regulation in frontline service roles.